Mapping the Nephron Exercise Incorporates Multiple Learning Strategies - Mari K. Hopper; Maria A. Anderson; Sarah N. Lipp (Association of American Medical Colleges, 2017)
Introduction Understanding the location and action of nephron transporters and channels is important to the understanding of renal function. As each region of the nephron is unique in its inclusion of specific transporters and channels, mapping of the nephron is an effective first step in understanding overall nephron processing. We describe a small-group, active-learning exercise that facilitates students' ability to understand renal processing within each region of the nephron. Methods Following an overview lecture on renal transporters and channels, small groups of students worked cooperatively to map the nephron. This 2-hour, collaborative exercise was developed to reinforce key concepts in renal processing of ions and nutrients and, at the same time, utilize effective learning strategies. Learning strategies incorporated in this exercise include small-group collaboration, peer teaching, retrieval practice using an audience response system, and elaboration through discussion. Results Written examination was used to assess student understanding. Students demonstrated higher performance on a subset of questions related to this learning activity compared to the overall exam. Highly positive feedback was provided by a convenience sample of students completing an anonymous survey. Discussion This nephron-mapping exercise was an effective means to promote synthesis and analysis of lecture content and engage students in methods that enhance learning.